Identification of trends in socio-economic development of the regions of Kazakhstan - A. B. Turysbekova; A. K. Omurzakova (Экономика: стратегия и практика, 2021)
The peculiarities of the regional development of Kazakhstan, the variety of production, the initial level of resources in different regions, various reforms of the market economy have led to the uneven development of the regions of Kazakhstan. A region or regional economy is a subsystem of the “national economy” macrosystem. And the national economy is the internal system of the global world economy. Regional development is development based on three characteristics and qualities: interrelated stability, proportionality and social orientation. Basically, the effective development of an individual region means the use of certain factors and potentials through the creation of value in a market economy. However, it is not possible to have a common development strategy for the whole regions. Because each region has its own conditions of development, economic and social potential. Therefore, these factors should be taken into account in the development of the regional economy. The main task of the regional policy of Kazakhstan is to increase the competitiveness of the region in a market economy, employment and living standards of the population of the region through the full use of its production and resource potential. The purpose of this article is to identify trends in the socio-economic development of the regions of Kazakhstan. The article defines the concepts of “region”, “regional development” as a system and gives their main characteristics. Trends in the socio-economic development of the regions of Kazakhstan were determined by grouping the regions of Kazakhstan on the basis of socio-economic indicators and analysis of statistical data and facts. In conclusion, it was noted that the socio-economic development of the regions of Kazakhstan is at a high level. Today, the socio-economic development of the regions of Kazakhstan is much higher than in previous years. This means that the development of certain regions means an increase in the quality of life, employment, economic growth of the country.